Om at forstå Bibelen i den moderne verden: skriften som grundlaget for en verden af tegn med fire dimensioner - Theißen, Gerd (Dansk teologisk tidsskrift, 2011)
Resumé The article gives an outline of New Testament hermeneutics based on a hermeneutic of religion. Religions are sign worlds constructed by human beings. They refer to transcendence, a foundational story, imply moral imperatives, and form a community. The Bible is the basis of the Christian sign world that is constructed by two axioms (monotheism and Christology) and many basic beliefs. The Bible interprets and initiates religious experience. The basic religious experiences are: an amazement of the mystery of being, an experience of absolute confidence and of responsibility (cf. Ludwig Wittgenstein). These experiences pervade all four dimensions of the Bible: a kerygmatic message based in transcendence, a historical reference to the history Jesus, an ethical impact, and a canonical dimension, i.e. a relationship to churches. In modern times this implies a relationship to other religions. The article suggests therefore an edition of the Bible with an inter-religious appendix.
Gesehen am 25.06.2021
Keywords: Kerygma; Entmythologisierung; Religiöse Erfahrung; Bibel; Hermeneutik